Changes in insulin requirements during pregnancy in Japanese women with type 1 diabetes - Kambara, Misa (Diabetol Int, 2018)
AIMS: We investigated the changes in insulin requirements, and other relevant factors, in pregnant Japanese women with type 1 diabetes. METHODS: This retrospective observational study was conducted on 77 singleton pregnant women with type 1 diabetes, treated with multiple daily injections of insulin. We examined changes in daily insulin dose during pregnancy and defined the increased insulin doses as the ratio of maximum dose to the pre-pregnancy dose. The relationship between the increased insulin doses and maternal features or pregnancy outcomes was investigated. RESULTS: The insulin dose gradually increased during pregnancy, reaching a maximum dose that was 1.6 times of that prior to pregnancy, at 35 weeks of gestation. A negative significant correlation was observed between the insulin dose increases and duration of diabetes (p = 0.008). Greater increases in insulin doses were noted in women with multiparity, compared to nulliparity (p = 0.047). Multiple regression analyses revealed that shorter duration of diabetes was independently associated with the increases in insulin dose during pregnancy. CONCLUSIONS: Women with a longer duration of diabetes required smaller increases in insulin dose during pregnancy, suggesting that long diabetic duration may decrease placental function. Further investigations are needed to clarify the mechanisms that the duration of diabetes influences on insulin requirement during pregnancy.